Técnicas grafoplásticas para el desarrollo de la pinza digital en niños de educación inicial - Saltos Sisa, Elsa Geovanna (2025)
At the early education stage, children need to strengthen fine motor skills, such as the digital pincer, which involves the use of the thumb and index finger to grasp small objects, which is essential in the acquisition of writing skills to hold the pencil. In view of its importance, the objective was to analyze how graphoplastic techniques can contribute to the development of this fine motor skill. The methodological approach used was eminently qualitative, it was situated as a